The role of Desmozoon lepeophtherii in complex gill disorder of Atlantic salmon (Salmo salar) - Herrero-Fernandez, Ana (University of Stirling, 2019)
Gill disease is an important challenge for Atlantic salmon (Salmo salar L.) aquaculture worldwide. Complex gill disorder (CGD) is a multifactorial and multiaetiological condition that tends to occur from late summer to early winter in salmon. The microsporidian Desmozoon lepeophtherii has been associated with CGD, but the interaction between the pathogen and its host remains to be understood. This thesis examines different aspects of D. lepeophtherii in an attempt to clarify the role and significance of D. lepeophtherii in CGD. Spores from D. lepeophtherii, derived from the sea lice (Lepeophtheirus salmonis) were used to infect different fish cell lines (rainbow trout gill cells and salmon head kindey cells) and primary macrophage cultures from Atlantic salmon head kidney in vitro. However, there was no evidence of D. lepeophtherii replication in any of the cultures. A one-year longitudinal study was carried out at two marine salmon farms to determine the correlation between gill pathology and the putative pathogens associated with CGD (D. lepeophtherii, Candidatus Branchiomonas cysticola and salmon gill pox virus (SGPV)), as well as Paramoeba perurans, the aetiological agent of amoebic gill disease (AGD). The two farms were positive for the four pathogens, with Ca. B. cysticola and D. lepeophtherii being the most frequently detected agents, and SGPV detected sporadically throughout the study. Paramoeba perurans was detected in the two farms but an outbreak of AGD only occurred in one of the farms. Statistical analysis of the data from the two farms showed that variations in SGPV and Ca. B. cysticola loads were not associated with an increase in the gill score (p>0.05), while D. lepeophtherii and P. perurans were (p< 0.001), although obvious pathology associated with D. lepeophtherii infection was not evident. An in situ hybridisation (ISH) method was developed to detect the developmental and spore stages of the parasite, the sensitivity (92%) of which was higher than other staining methods currently used ...